Google Classroom based project learning on Science Literacy - Kusuma Dayu, Dian Permatasari; Aprilia, Septi; Hakim, Pratiwi Rahmah; Kurniawati, Rissa Prima; Rulviana, Vivi (Dharmas Education Journal (DE_Journal), 2025)
During this COVID-19 period, all activities, especially education, are carried out at home. Using online learning media, such as Google Classroom, has led to online learning (in the network). This study aims to generate and determine the effectiveness of online learning using Google Classroom based on project-based learning on scientific literacy. This research method uses the type of research and development with the ADDIE development model. The stages in the ADDIE model consist of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. Data collection techniques used are test and non-test. The subjects in this study were elementary school students. From the research results obtained from the validation results of learning materials and media, the results of the assessment of Google Clasroom learning media based on project learning on scientific literacy obtained a percentage of 95% with the category "Very Valid" and the results of the validation of learning media obtained a percentage of 92%. So based on these results, this Google Clasroom based on project learning media product is suitable for use during the learning process at school.The result of the development of this learning media is a project-based learning media based on Google Classroom. It can be concluded that Google Classroom learning media based on project-based learning is suitable for use in online learning and improving students' scientific literacy.